Study on failure mechanism and mechanical properties of casing joints of square steel confined concrete arch. (October 2018) - Li, S.C.; Lu, W.; Wang, Q.; Sun, H.B.; Jiang, B.; Qin, Q.
Abstract: Square steel confined concrete (SQCC) arch has broad application prospects as a high-strength support form in underground engineering. A reasonable selection of arch connection joint is the premise of the calculation for the support structure design. However, there are few researches on SQCC connecting joints. As an important connection form of SQCC support structure, the casing joint is clear in force transmission and convenient in construction in practical application. At present, all the casing joints are simply considered as ideal components with equivalent stiffness while calculating the internal force of SQCC arch, but the actual stress state and failure mode of the joint have not yet been discussed in depth. In order to grasp the bearing mechanism of SQCC arch joints, a simplified calculation model of the joints is established; two typical failure modes of the casing joints are proposed; the failure criterion of casing joint is deduced; and its calculation method of flexural capacity is established. In addition, the pure bending laboratory experiment and numerical experiment of the casing joint specimen are carried out, a depth analysis is made on the deformation process and failure mode of the casing joint; and the correctness of the above theoretical analysis is verified. Based on the M ‐ θ curve, the influence of each parameter is analyzed on the mechanical property of the joint and therefore, a series of principles of casing joint design are proposed. The research results could provide a theoretical basis for the design and application of related projects. Highlights: A simplified calculation model of the casing joints is established. Two typical failure modes of casing joint are proposed. A criterion of bending failure mode of casing joint is established. A calculation method of bearing capacity of casing joint is established.